Construction of a georeferenced house data set for the city of Trier within the MikroSim project - Jan Weymeirsch; Hanna Dieckmann; Ralf T. Münnich (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2024)
Spatial dynamic microsimulations have distinct potential to operate and project populations on finely detailed geographic level. For this, a detailed building and dwellings data set is typically needed, such that inner-region migration flows and local population developments may be modelled accurately. There exists, however no comprehensive building register for Germany, especially none that is openly available to the research community and which accurately distinguishes buildings in regard to their usage as accommodation or as potential workplaces. The following work serves as a pilot study to create such a data set by combining several publicly available data sources for a single region in Germany. Its quality is evaluated by comparing it to both, aggregate information from German official statistics, and register data from the city of Trier.
Keywords: 330; Gebäude; Kartographie; Mikrosimulation; Räumliche Interaktion; Trier (Region)